2015
DOI: 10.1177/0093650215619215
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Persuasion From Virtual-World Campaigns

Abstract: With the general public spending increasing amounts of time in virtual gaming worlds, it is relevant to explore social influence dynamics that can occur in virtual reality settings. Three studies tested the hypothesis that transportation into a virtual game heightens susceptibility to influence from in-game health communications. Study 1 participants played a first-person shooter game that had either landscape paintings or graphic anti-DUI (drive under the influence of alcohol) messages embedded in the backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 77 publications
0
8
1
2
Order By: Relevance
“…39 Research drawing on narrative transportation theory suggests that when a player is immersed in a game, the game world is experienced as "real." [26][27][28]40 When players stop playing, they exit as they would real space, taking with them memories, emotions and the sense of having been in a place. 41 Thus, after spending time in a fictional environment where tobacco use is normalized, players, particularly those controlling smoking characters, some whose skills are enhanced by tobacco use, may be primed to take up smoking in real life.…”
Section: Discussionmentioning
confidence: 99%
“…39 Research drawing on narrative transportation theory suggests that when a player is immersed in a game, the game world is experienced as "real." [26][27][28]40 When players stop playing, they exit as they would real space, taking with them memories, emotions and the sense of having been in a place. 41 Thus, after spending time in a fictional environment where tobacco use is normalized, players, particularly those controlling smoking characters, some whose skills are enhanced by tobacco use, may be primed to take up smoking in real life.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between immersion in a game and persuasion has been studied by Burrows and Blanton [25]. They have used transportation theory, finding that transportation into a virtual game made players more susceptible to persuasion by means of an in-game health message.…”
Section: Immersion and Persuasionmentioning
confidence: 99%
“…Murray's (1997) [24] research of narrative structures in novels and films has been instrumental in this respect as she established that narratives with multiple contradictory alternatives required active participation of the audience resulting in them feeling to be part of the unfolding story. Research about digital entertainment games also showed that high immersion led to increased receptivity for the persuasive message [25]. There is, however, an important difference between entertainment games and persuasive games.…”
Section: Introductionmentioning
confidence: 99%
“…17 When young adults (mean age 19) were exposed to anti-DIU (driving while under the influence) messages in an first-person-shooter video game, they indicated they were less willing to engage in DUI than those not exposed. 18 In a meta-analysis, video game players who played games that depicted risky behavior had increased risk-taking inclinations, with video game playing demonstrating a stronger effect than more passive media like movies or television. 19 Knowing the type of tobacco content in video games is thus important for considering how to develop effective tobacco control strategies for this media type.…”
Section: Theory Of Presence and The General Learning Modelmentioning
confidence: 99%